PENGEMBANGAN E-MODUL BIOLOGI BERBASIS PROBLEM BASED LEARNING PADA MATERI PEMBELAJARAN SISTEM KOORDINASI KELAS XI SMA - Tendi Hengki Saputra; Anak Agung Oka; Widya Sartika Sulistiani (EDUBIOLOCK, 2021)
The use of learning media helps an educator in the process of facilitating learning in class and helping students in the learning process. Media is an important element in improving learning process quality in class. The development research in this research was developed in the form of E-module teaching materials using potential and problem procedures, studying data, product design, design validation, design revision, product testing, and product revision. The final result of the design expert gets an initial percentage value of 90% after revision gets 98%. The final results of the expert test obtained an initial percentage value of 94.77% after revision which is 97.31%. The final results of the small group trial obtained a percentage value of 86% with the criteria "good". Biology E-module products based on Problem-Based Learning are feasible to be used or tested on students.